Understanding Connective Action in the Wadas Village Conflict: Social Network Analysis on the #WadasSuing Hashtag - Dini Kumalawati Sarjani (Universitas Medan Area, 2023)
The conflict that occurred in Wadas Village is a conflict that originated from a grassroots movement, has been going on for several years since 2013, and has not been resolved until now. In addition to conducting movements through offline actions, the community and non-governmental organizations that oppose mining plans also make efforts to spread actions and foster support by using social media. Connective action theory is used in this research, it is important to know the power of the #Wadasmengault hashtag who are the actors, and the network structure formed in this online movement. The method used in this research is Social Network Analysis (SNA). Data collection was carried out using Netlytic software, The results obtained are that the hashtag #Wadas Mengtinggian as an extension of offline action was less successful. Because the Reply, retweet, and mention activities are one-way. The dominant actors in hashtag conversations are NGO accounts and environmental organizations, the delivery of information only spreads among them and does not spread naturally to the wider community